Deep model of lithosphere of central part of the Antarctic peninsula from DSS data and high pressures petrophysics - Korchin, V. A.; Burtny, P. A.; Karnaukhova, E. E.; Chulkov, S. S. (Ukrainian Antarctic Journal, 2010)
Models of mineral matter distributing with a depth along seismic DSS 10, 12, 13 profiles near the station «Academik Vernadsky» are built.